Cover Image, Volume 4, Issue 2. Issue 2 (28th June 2021) - Ahammed, Tanvir; Anjum, Aniqua; Rahman, Mohammad Meshbahur; Haider, Najmul; Kock, Richard; Uddin, Md Jamal
Abstract : The cover image is based on the Research Article Estimation of novel coronavirus (COVID‐19) reproduction number and case fatality rate: A systematic review and meta‐analysis by Tanvir Ahammed et al., https://doi.org/10.1002/hsr2.274 .